(untitled) (Research, Society and Development, 2023)
Wheat flour is the main ingredient used in the manufacture of bakery products, due to its ability to form a viscoelastic network, capable of retaining gas during the dough fermentation stage. However, there is a demand for gluten-free products to serve populations that have food consumption restrictions, such as allergies, intolerances, or sensitivity to wheat components. The aim of this review was to present the main raw materials that have been used as alternatives to wheat flour for the preparation of gluten-free bakery products. This way, a search was carried out in the main databases: Google Scholar, SciElo, Scopus, PubMed, Lilacs, Web of Science, using terms related to the subject such as gluten intolerance, celiac disease, wheat allergy and gluten-free flours. Fifty-three studies were selected, published in the period from 2012 to 2022. From this survey, it was observed that most studies are directed to the development of gluten-free cookies and breads. The main materials used were rice, pea, amaranth, and soy flours, which were usually used in combinations, depending on the purpose, such as providing crispness (texture) to cookies or softness to breads, and cakes. In addition, it was observed that the choice of raw materials also considers the nutritional balance, since in most studies the formulations were developed using combinations of protein, starchy and fibrous sources.